Seminar Nasional : raktualisasi dan refleksi kurikulum 2013 - Seminar_Nasional_:_raktualisasi_dan_refleksi_kurikulum_ 2013 (Mandiri Graffindo Press dan Prodi PGMI UIN Sunan Kalijaga, 2013)
et,1/irh,c.1